2009
DOI: 10.1111/j.1476-5381.2009.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic antibodies: successes, limitations and hopes for the future

Abstract: With more than 20 molecules in clinical use, monoclonal antibodies have finally come of age as therapeutics, generating a market value of $11 billion in 2004, expected to reach $26 billion by 2010. While delivering interesting results in the treatment of several major diseases including autoimmune, cardiovascular and infectious diseases, cancer and inflammation, clinical trials and research are generating a wealth of useful information, for instance about associations of clinical responses with Fc receptor pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
966
0
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,191 publications
(985 citation statements)
references
References 83 publications
(92 reference statements)
6
966
0
13
Order By: Relevance
“…Most of these mAbs (9/15) are human immunoglobulin G1 (IgG1) that trigger various mechanisms, such as target signaling inhibition, apoptosis, activation of the classical complement pathway, and/or of immune effector cells expressing Fcg receptors (FcgR; refs. 1,2). Although it is difficult to assess the contribution of each of these mechanisms in their in vivo efficacy, clinical trial results support an important role of antibody-dependent cell-mediated cytotoxicity (ADCC) for both lymphomas and solid tumors (3).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these mAbs (9/15) are human immunoglobulin G1 (IgG1) that trigger various mechanisms, such as target signaling inhibition, apoptosis, activation of the classical complement pathway, and/or of immune effector cells expressing Fcg receptors (FcgR; refs. 1,2). Although it is difficult to assess the contribution of each of these mechanisms in their in vivo efficacy, clinical trial results support an important role of antibody-dependent cell-mediated cytotoxicity (ADCC) for both lymphomas and solid tumors (3).…”
Section: Introductionmentioning
confidence: 99%
“…Biopharmaceuticals are a fast growing class of therapeutics (1)(2)(3)(4). Assessment of pharmacokinetics (PK) and pharmacodynamics (PD) is an integral part of preclinical and clinical development (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Intense research efforts have been dedicated to predict and reduce immunogenicity 246 . In line with the huge success of monoclonal antibodies since the late 1990's 247 , the administered doses have massively multiplied 248 . On the other hand, in a study with twenty-eight single clonal CHO cell lines, correlations were identified between the antibody titer and the level of both aggregation and low-molecular species 249 .…”
Section: Introductionmentioning
confidence: 99%